ChemInform Abstract: Synthesis and Structure of Novel Ag2Ga2SiSe6 Crystals: Promising Materials for Dynamic Holographic Image Recording. Issue 49 (17th November 2016) - Piasecki, M.; et al.
Abstract: The AgGaSe2 —SiSe2 binary phase system is explored in steps of 5 mol% (evacuated quartz containers, 1.